2018
DOI: 10.5999/aps.2017.01375
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality and dynamic infrared thermography for perforator mapping in the anterolateral thigh

Abstract: Dynamic infrared thermography (DIRT) has been used for the preoperative mapping of cutaneous perforators. This technique has shown a positive correlation with intraoperative findings. Our aim was to evaluate the accuracy of perforator mapping with DIRT and augmented reality using a portable projector. For this purpose, three volunteers had both of their anterolateral thighs assessed for the presence and location of cutaneous perforators using DIRT. The obtained image of these “hotspots” was projected back onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 17 publications
(25 reference statements)
1
38
0
Order By: Relevance
“…8 An additional study utilized a portable infrared thermography device to identify perforators of the anterolateral thighs of three volunteer subjects. 9 These support our hypothesis that this technology can be used to monitor free flaps in the postoperative period.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…8 An additional study utilized a portable infrared thermography device to identify perforators of the anterolateral thighs of three volunteer subjects. 9 These support our hypothesis that this technology can be used to monitor free flaps in the postoperative period.…”
Section: Introductionsupporting
confidence: 75%
“…1,2,11,12 They have also been used to identify vascular perforators and flap integrity intraoperatively. [5][6][7][8][9] The application of thermal imaging technology or many other flap monitoring techniques involve the use of equipment with significant cost in the medical device marketplace.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the use of AR in reconstructive microsurgery was explored in five studies, consisting of 30 patients (►Table 2). [14][15][16]24,25 AR was evaluated in a bilateral lower limb lympho-venous anastomosis, 20 seven anterior lateral thigh flaps, 21,28 one latissimus dorsi flap, 25 one tensor facia lata flap, 25 15 deep inferior epigastric perforator (DIEP) flaps, 11,21 three medial sural artery perforator flaps, and three posterior tibial artery perforator flaps. 12 All of these studies demonstrated a level of evidence of four with the exception of the study from Nishimoto et al that showed a level of evidence of five (►Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these limitations, Cifuentes et al evaluated the use of projection-based AR whereby digital data are physically superimposed by means of projection onto the surface of the skin. 28 The authors combined the capabilities of a thermal camera and a portable projector to project a thermal map of anterolateral thigh perforators onto the surface of the skin on volunteers. This study identified an average of five perforators in the area of interest, which correlated 100% with hand-held Doppler findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation